Công văn số 53A/TANDTC-TH ngày 30 tháng 5 năm 2016 của tòa án nhân dân tối cao về việc triển khai tháng hành động phòng, chống ma túy (2016)
Công văn số 53A/TANDTC-TH ngày 30 tháng 5 năm 2016 của tòa án nhân dân tối cao về việc triển khai tháng hành động phòng, chống ma túy.